Керамические химически стойкие изделия - Зайонц Роберт Маркович (Стройиздат, 1966)
Экземпляры: КХ (20170412) / Инвентарный номер: 401734 / Цена: 0.74 / Сис.шифр: 666.7 / Авт.знак: З-17 / ГРНТИ: 80.31.37 / ББК: 35